Narrative assessment methods in children: a systematic review - Mahbubeh Nakhshab; Maryam Arabpour; Yalda, Kazemi (Vesnu Publications, 2014)
Abstract Introduction: Narrative abilities have been shown as good predictors of reading skills and academic achievements. Assessment of narrative skills includes two parts of macro- and micro-structures. The current review systematically investigates narrative studies in terms of describing and comparing different narrative assessment methods to report adequacy of the methods in various contexts. Materials and Method: The search strategy included key words like "narrative skills", "narrative in children", "language skills assessment" and "narrative assessment tool". Data bases included ASHA publication, PubMed, Science direct, Google Scholar, Cochrane, Wiley, IranMedex, IranDoc, and SID between 1946 and 2014. The abstract and title of papers were evaluated based on inclusion/exclusion criteria. Results: Sixty one out of 105 published documents were eligible to be reviewed. The reviews showed that children's oral narratives are assessed through language samples. Various methods have been developed to measure children's narrative skills including story generation, story retelling, and personal narratives. Moreover, different narrative assessment tools are developed to assess either narrative production or narrative comprehension in both levels of micro- and macro- structures. Except for Narrative Assessment Protocol (NAP), scoring procedures in other tools is transcription. Discussion: Familiar pictures and story retelling provide more complex and longer narratives. Narrative generation task is more difficult than narrative retelling task and is more capable to differentiate language disabilities. Narrative assessments recently available in Iran include NAP, SRT, and ENNI. Among them, it has been claimed that NAP is more user-friendly due to the convenient of online scoring procedure which needs further research.   Key words: narrative, narrative assessment, language skills, children, systematic review